2001
DOI: 10.1016/s0925-4439(01)00030-8
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase-derived reactive oxygen metabolites contribute to liver necrosis: protection by 4-hydroxypyrazolo[3,4-d]pyrimidine

Abstract: Xanthine oxidase (XO) generates reactive oxygen metabolites (ROM) as a by-product while catalyzing their reaction. The present study implicates these ROM in the pathogenesis of liver necrosis produced in rats by the intraperitoneal administration of thioacetamide (TAA; 400 mg/kg b.wt.). After 16 h of TAA administration, the activity of rat liver XO increased significantly compared to that of the control group. At the same time, the level of serum marker enzymes of liver necrosis (aminotransferases and alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…XO is thought to be one the most important source of ROS [25,26]. TAA generates liver damage by upregulating hepatic XO activity [2]. This feature of TAA makes it a proper hepatotoxic agent for testing the effects of XO inhibition [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…XO is thought to be one the most important source of ROS [25,26]. TAA generates liver damage by upregulating hepatic XO activity [2]. This feature of TAA makes it a proper hepatotoxic agent for testing the effects of XO inhibition [3].…”
Section: Discussionmentioning
confidence: 99%
“…Despite technological advances and improvement in intensive care conditions, ALF continues to be one of the most challenging problems in clinical practice [1]. In various liver injury models [2][3][4][5], it has been revealed that increased xanthine oxidase (XO) activity plays pivotal role in the oxidative stress-induced hepatic damage. XO is widely distributed throughout various tissues with the highest level in the liver [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models include various forms of liver injury, i.e., ones induced by ionizing radiation (Srivastava and Kale, 1999;Srivastava et al, 2002), ethanol (Oei et al, 1982;Lieber, 1997;Kono et al, 2000;Zima et al, 2001), cocaine (Aoki et al, 1997), thioacetamide (Ali et al, 2001), acetaminophen (Knight et al, 2001), and aluminum (Moumen et al, 2001). In the case of ethanol, aluminum, and radiation, enhancement of hepatic XO levels and/or spillage of XO into the circulation were detected (Oei et al, 1982;Zima et al, 1993;Moumen et al, 2001;Srivastava et al, 2002).…”
Section: G Xanthine Oxidase and Various Forms Of Toxic Organ Injurymentioning
confidence: 99%
“…They are also released from macrophages in response to bacterial invasion, and are generated as by-product during the enzyme catalysed reactions. 52,53 NF-B activation is associated with free radical generation and precedes, for example, pathological liver injury in experimental alcoholic liver diseases. 54 The viral protein NS5A, which activates NF-B, is observed to alter intracellular [Ca 2þ ] and induce oxidative stress.…”
Section: Introductionmentioning
confidence: 99%